Chemical composition and nutritional properties of Gastrodia elata water extract and its effects in rats with streptozotocin–induced diabetic osteoporosis - Jia, Fanfan; Kang, Sirui; Li, Xinxin; Quan, Yiheng; Gao, Ruiqing; Chen, Chen (Frontiers in Nutrition, 2025)
IntroductionGastrodia elata Blume (G. elata) is an edible medicinal homologous plant with a long history of use. However, to date, there is no evidence of the nutritional components and anti-diabetic and osteoporotic effects of the water extract of G. elata (WGE).MethodsIn this study, WGE was prepared and analyzed for moisture, ash, protein, lipid, mineral, amino acid, total phenolic, and flavonoid content. WGE was analyzed using ultra-high performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF/MS). Furthermore, the effect of WGE on streptozotocin-induced osteoporosis in diabetic rats was explored, along with an in-depth examination of the underlying mechanisms.ResultsThe results indicated that WGE reduced blood glucose, water, food intake, and body weight and improved Hyperglycemia and organ coefficients. WGE treatment noticeably increased bone mineral density (BMD), repaired bone morphology (BM), restored bone histomorphometric parameters, and ameliorated pathological pancreatic lesions in diabetic rats. It significantly elevated the activity of glutathione (GSH), superoxide dismutase (SOD), and catalase in liver tissues, osteoblast numbers, and the mRNA and protein expression of osteoprotegerin (OPG) and runt-related transcription factor 2 (Runx2). WGE treatment reduced serum inflammatory cytokine levels and the number of osteoclasts and bone marrow adipocytes.ConclusionThe protective effect of WGE against diabetic osteoporosis arises from several mechanisms: lowering blood glucose levels, inhibiting oxidative stress and inflammation, and modulating OPG/receptor activator of nuclear factor-κB ligand (RANKL) expression. Our results indicated that WGE could serve as a theoretical foundation for the treatment of diabetic osteoporosis.